E-Government and smart cities: contexts and challenges taking from digital usage and exploration - Gouveia, Luis Borges (2020)
e-Government and Smart Cities: Contexts and Challenges Taking from Digital Usage and Exploration The current context is both complex and challenging. Also, considering the usage and exploration of the digital this includes an even greater complexity resulting from time space alternatives. For both nations and states, such challenges are in place and force digital transformation. Such challenges are critical for their existence as we known them. As so, we are on need of further knowledge in order to develop new solutions for old and new problems. This seminar proposes a visit to conducted research from the *TRS group since 2013 related with e-Government and smart cities and to discuss potential new projects. It starts by discussing the context and the road done to provide insights on the road ahead.